Sulfur and phosphorus co-doping of hierarchically porous graphene aerogels for enhancing supercapacitor performance - Yu, Xu; Kang, Yingbo; Park, Ho Seok (Carbon (New York), 2016)
The control in the heteroatom doping is critical for surface and electronic properties, but chemistry is more complicated when two or more heteratoms are incorporated. Herein, we have demonstrated the co-doping of sulfur (S) and phosphorus (P) atoms into the three-dimensional (3D) macroporous, activated graphene aerogel (SP-AG). The C–S and C–PO bondings as major functional groups are simultaneously incorporated into the surface of SP-AG. Despite the high loading of S and P of 5.8 and 4.6%, respectively, the 3D macroporous continuity is preserved. The specific capacitance of SP-AG is 438 F/g at 10 mV/s is much greater than 347, 313, and 240 F/g of S-AG, P-AG, and AG, respectively. Moreover, the SP-AG delivers a specific capacitance of 381 F/g as a scan rate is increased to 500 mV/s, indicating the capacitance retention of 87.2%. After 10000 charging/discharging cycles at current density of 1 A/g, the SP-AG shows a greater electrochemical stability than AG with the capacitance retention ratio of 93.4%, due to the synergistic effect of S and P co-doing and 3D architecture. This synergistic effect of composition and structure is further confirmed by the enhanced energy and power densities in organic and ionic liquid electrolytes.